2013
DOI: 10.1007/s00484-013-0666-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat accumulation period in the Mediterranean region: phenological response of the olive in different climate areas (Spain, Italy and Tunisia)

Abstract: The main characteristics of the heat accumulation period and the possible existence of different types of biological response to the environment in different populations of olive through the Mediterranean region have been evaluated. Chilling curves to determine the start date of the heat accumulation period were constructed and evaluated. The results allow us to conclude that the northern olive populations have the greatest heat requirements for the development of their floral buds, and they need a period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 32 publications
3
41
2
Order By: Relevance
“…In this regard, Galán et al (2005) found different Tb values for accumulating thermal time until flowering in olive depending on the values of average air temperatures at different sites in Andalusia (Spain). Aguilera et al (2014) also reported over a wide latitudinal gradient from central Italy (43°N) to southern Tunisia (33°N) that more southerly olive populations had lower thermal time requirements than those in the north. It is possible that the warm temperatures in our area may have resulted in physiological changes within the tree and its buds that led to deviations from the DMA model calculations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In this regard, Galán et al (2005) found different Tb values for accumulating thermal time until flowering in olive depending on the values of average air temperatures at different sites in Andalusia (Spain). Aguilera et al (2014) also reported over a wide latitudinal gradient from central Italy (43°N) to southern Tunisia (33°N) that more southerly olive populations had lower thermal time requirements than those in the north. It is possible that the warm temperatures in our area may have resulted in physiological changes within the tree and its buds that led to deviations from the DMA model calculations.…”
Section: Discussionmentioning
confidence: 82%
“…Expansion of olive production to lower than traditional latitudes requires information about the flowering response of different cultivars to key environmental factors such as temperature (Orlandi et al, 2010b;Aguilera et al, 2014). Because field trials in perennial A consideration not accounted for in the DMA model is whether a maximum threshold for thermal time accumulation to flowering exists after endodormancy release.…”
Section: Discussionmentioning
confidence: 99%
“…High temperatures during the two months preceding budburst have a positive effect on the final fruit production. According to Aguilera et al (2013), the onset of the heat accumulation period usually occurs in the first two weeks of February, and a certain number of days are required to completely satisfy the olive tree biothermic requirements. The relationship between accumulation of temperature and future development of flowers and fruit might explain the inclusion of this variable in the forecasting models.…”
Section: Discussionmentioning
confidence: 99%
“…Both the onset of the heat accumulation period and the temperature threshold for the number of positive heat units might vary according to the climate of a determined geographical area. The threshold level was also reported to decrease towards the north (Aguilera et al, 2013). Altitude is the topographical factor that most influences olive local phenology and the major weather factors are temperature, rainfall, and solar radiation, which control plant evapotranspiration .…”
Section: Introductionmentioning
confidence: 99%
“…Several wider-area studies were also undertaken to aim at more general statistical characteristics of the season, e.g. Aguilera et al (2014Aguilera et al ( , 2013, Galan et al (2016).…”
Section: Introductionmentioning
confidence: 99%